STRATEGI PENGELOLAAN USAHA TANI PADA PERKEBUNAN RAKYAT DI KAWASAN PERBATASAN PULAU SEBATIK - Muhamad Tulodo Adisono; M Yanuar J Purwanto; Sri Mulatsih (Universitas Medan Area, 2018)
This research was conducted with the aim of knowing land use pattern, farmer earnings analysis, sustainability analysis and establishing effective strategy used to manage banana farming in Sebatik area. The method used is survey by using data that is quantitative and analysis using statistical media. Spatial analysis compares between existing land use and spatial plan. Analysis of farming using RC ratio analysis yields all commodities in the border area for every Rp 1.00 the cost incurred will generate revenue into the profitable category because the R / C value> 1. Data analysis using RAP-FARM with multidimensional scaling method (MDS) . The results show that the status of sustainability of farm management in border area is quite sustainable. (56,064). Five priority strategies are: (a) Agro-tourism development (b) Improve marketing and skills to manage sustainable agriculture resources. (c) Increasing the intensity of cultural events (d) and using agricultural technology effectively and efficiently (e) Optimizing the institutional function. Key Factors: Strategy, Sustainability, Boreder, MDS, SWOT